The Emotional States Elicited in a Human Tower Performance: Case Study - Damian-Silva, Sabrine; Feixa, Carles; Prat, Queralt; Luchoro-Parrilla, Rafael; Pic, Miguel; Rillo-Albert, Aaron; Sáez de Ocáriz, Unai; Costes, Antoni; Lavega-Burgués, Pere (Frontiers in Psychology, 2021)
Human Towers are one of the most representative traditional sporting games in Catalonia, recognized in 2010 as Intangible Cultural Heritage by the United Nations Organization for Education, Science and Culture (UNESCO). The objective of this research was to study the emotional states (well-being, discomfort and affectivity) elicited by a representative performance of the colla de Castellers de Lleida. This research is based on an ethnographic case study, with mixed methods in which seventeen key informants (castellers) voluntarily participated. Participant observation was used; the data were recorded in a field diary and oral sources (semi-structured interviews). The content analysis was done using the Atlas.ti software (version 8.4.4). An SPSS database was also created. The statistical techniques were: Descriptive statistical techniques, cross tables with Pearson's Chi-square values (significance level of p <.05). We also used a classification and regression trees (CRT) to examine the predictive capacity of five independent variables (data source, logic, semantic units; contexts of a performance) of emotional states. The results reveal that the comments (n = 132) were mostly oriented towards wellbeing states (n = 70; 53%), The internal cooperative logic of the Human Towers enhances the intense interpersonal relationships of socio-emotional well-being.